2015
DOI: 10.1186/s12889-015-1739-9
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions and experiences of people injured in motor vehicle crashes in a compensation scheme setting: a qualitative study

Abstract: BackgroundThe evidence that compensation related factors are associated with poor recovery is substantial but these measures are generic and do not consider the complexity of scheme design. The objectives of this study were to understand people’s perceptions and experiences of the claims process after sustaining a compensable injury in a motor vehicle crash (including why people seek legal representation); and to explore ways to assist people following a compensable injury and improve their experience with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…However, the findings also suggest that early referral of the CTP cases did not necessarily lead to favourable patient outcomes, and this may have resulted from secondary gain motivations created by CTP lump sum payments. Current research supports that the complexity of the claims process and the requirements of legal representation in the CTP compensation setting contribute to poor injury and mental health recovery, which in turn may pose additional challenges for psychologists (Murgatroyd, Lockwood, Garth, & Cameron, ). However, with the new CTP scheme commencing in December 2017 and reforms including lump sum payments being limited to serious injuries, psychologist's capacity to implement EBP should be increased.…”
Section: Discussionmentioning
confidence: 90%
“…However, the findings also suggest that early referral of the CTP cases did not necessarily lead to favourable patient outcomes, and this may have resulted from secondary gain motivations created by CTP lump sum payments. Current research supports that the complexity of the claims process and the requirements of legal representation in the CTP compensation setting contribute to poor injury and mental health recovery, which in turn may pose additional challenges for psychologists (Murgatroyd, Lockwood, Garth, & Cameron, ). However, with the new CTP scheme commencing in December 2017 and reforms including lump sum payments being limited to serious injuries, psychologist's capacity to implement EBP should be increased.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, permanent or temporary disabilities arising from minor injuries pose an on‐going problem for the compensation and health‐care system . It has been acknowledged that this particular group is at risk of being left alone with problems and symptoms that are difficult to understand and often invisible to others …”
Section: Introductionmentioning
confidence: 99%
“…Other reasons suggested for a poor recovery, or even for permanent disability, include factors other than purely injury‐related ones. Few qualitative studies have identified factors that largely depend on a person's environment and health‐care and compensation systems . Others reported factors such as lack of family support, legal involvement and the compensation claim .…”
Section: Introductionmentioning
confidence: 99%
“…While their role and competencies may vary in the different countries, CMs relationship with the injured person may often be much longer than the duration of interaction with any health care providerit starts very soon after the event and may continue for years until claim resolution. Though, delayed treatment and payment approvals may hamper that relationship [12], based on their longitudinal familiarity with the hundreds of cases they manage each year, CMs represent a unique source of information on early predictors of recovery outcome. Additionally, their perspective is broader than most health care providers, because they interact with more of the key persons involved in the injuryincluding injured person, various health care providers, attorneys and family.…”
Section: Introductionmentioning
confidence: 99%